2009
DOI: 10.1590/s1677-55382009000100010
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and quality-of-life outcomes after autologous fascial sling and tension-free vaginal tape: a prospective randomized trial

Abstract: Purpose: Evaluate the impact autologous fascial sling (AFS) and tension-free vaginal tape (TVT) procedures on qualityof-life in incontinent women. Materials and Methods: Forty-one women were randomly distributed into two groups. Group G1 (n = 21), underwent AFS and group G2 (n = 20) TVT implant. The clinical follow up was performed at 1, 6, 12 and 36 months. Results: between groups. As regards the satisfaction rate, there was no statistical difference between groups. Analysis of quality of Conclusion: Similar … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 16 publications
0
20
0
Order By: Relevance
“…Amaro et al. compared subjective cure rates between TVT and AFS at 12 months and reported no difference (65% vs 57%, P = 2.24). Morgan et al.…”
Section: Discussionmentioning
confidence: 99%
“…Amaro et al. compared subjective cure rates between TVT and AFS at 12 months and reported no difference (65% vs 57%, P = 2.24). Morgan et al.…”
Section: Discussionmentioning
confidence: 99%
“…10 Amaro et al performed a randomized controlled trial comparing autologous fascia slings to synthetic mesh. 21 There was no difference in cure at 12 months (57 percent versus 65 percent), patient satisfaction, and quality of life. Sharifiaghdas and Mortazavi found similar findings in another randomized controlled trial comparing autologous fascia slings to synthetic slings.…”
Section: Plastic and Reconstructive Surgery • November Supplement 2012mentioning
confidence: 87%
“…In contrast, Bai et al found that autologous rectus fascia slings had a higher cure rate (93 percent) compared with retropubic colposuspensions (88 percent) and synthetic slings (87 percent) 23 (Table 2). [15][16][17][18][19][20][21][22][23][24][25] A recent meta-analysis concluded that traditional slings using a variety of materials (porcine dermis, dura mata, fascia lata, vaginal wall, autologous dermis, and rectus fascia) appear to be as effective as minimally invasive slings, but have higher rates of adverse events. 26 Patients with porcine dermal slings may be at an increased risk of urinary retention and reoperation because of variation in the host response to the biological material compared with the predictable response to polypropylene mesh.…”
Section: Plastic and Reconstructive Surgery • November Supplement 2012mentioning
confidence: 99%
“…Because of the higher efficacy and lower morbidity [13] several autologous (e.g. rectus fascia, vaginal wall and fascia lata) and synthetic (prolene or mersilene) materials are used as suburethral slings for the treatment of SUI in women [7]. Since its production, TVT has been shown to be as effective as fascial slings [14].…”
Section: Discussionmentioning
confidence: 99%
“…Several autologous and synthetic materials are used as suburethral slings for treating SUI in women. The use of synthetic materials decreases the duration of surgery, avoids the harvesting process, and seems to have a similar outcome to that from the fascial sling [7]. Special indications for autologous grafts include patients with a history of poor vaginal healing, pelvic bone trauma, pelvic radiotherapy, or previous urethral reconstruction [8].…”
Section: Introductionmentioning
confidence: 99%